Localization algorithm for wireless sensor networks - Ng, Wan Jing. (2011)
Location knowledge of nodes in a network is essential for many tasks such as routing, cooperative sensing, or service delivery in ad hoc, mobile, or sensor networks. Locating objects, such as keys, office equipment, people, or even an enemy vehicle, is even becoming an application that has received a lot of attention over recent years. There are many methods for node localization, such as Semi-Definite Programming and Shortest-Path Algorithm. In this Final Year Project (FYP), we will be focusing on the Least Square for node localization with a relatively small number of anchor nodes in a large network. It is an approach that is often used to solve over determined or inexactly specified systems of equations in an approximate sense. Instead of solving the equations exactly, least squares minimize the sum of the squares of the residuals. The aim of this Final Year Report is to study the performance of this Least-Square method and also to write an algorithm based on this method into a computer program, MATLAB. Also, an evaluation of its performance via computer simulation will be done as well. We will be examining how standard deviation of noise will affect the mean square errors of the least squares method and the least squares solution.